Determinants of Islamic banking financing in Indonesia: An empirical analysis of internal and macroeconomic factors - Rahmayanti, Dini; Batin, Mail Hilian; Suryati, Suryati; Ariyani, Diyah; Ifada, Khusnul (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
This article examines the internal and macroeconomic determinants affecting Islamic banking financing in Indonesia, focusing on Sharia Commercial Banks, Sharia Business Units, and Sharia People’s Financing Banks. Using a quantitative methodology with monthly panel data spanning from 2019 to 2022, the study employs Vector Autoregression (VAR) and Vector Error Correction Model (VECM) techniques. The analysis incorporates variables such as Total Assets, Third Party Funds (TPF), Net Operating Margin (NOM), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Return on Assets (ROA), Equivalent Rates of mudharabah and musyarakah, BI Rate, and Inflation. Findings reveal that in the long run, TPF, NOM, ROA, and the Equivalent Rate of Musyarakah positively influence Islamic banking financing, whereas NPF and inflation exert a significant negative impact. In the short run, TPF, NOM, ROA, and the Equivalent Rate of Mudharabah are significant influencers of financing. These results highlight the critical role of effective fund management and a stable economic climate in fostering the expansion of Islamic banking financing. The study offers valuable insights for policymakers and banking institutions aiming to improve financial inclusion and economic stability through enhanced Islamic banking practices.